2020
DOI: 10.1016/j.dsx.2020.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease (COVID-19): A systematic review and meta-analysis to evaluate the impact of various comorbidities on serious events

Abstract: Background and aims: Currently there is limited knowledge on medical comorbidities and COVID-19; we conducted a systematic review and meta-analysis to evaluate the impact of various morbidities on serious events in COVID 19. Methods: PubMed, Cochrane Central Register of Clinical Trials were searched on April 28, 2020, to extract published articles that reported the outcomes of COVID-19 patients. The search terms were "coronavirus" and "clinical characteristics". ICU admission, mechanical ventilation, ARDS, Pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
151
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 201 publications
(179 citation statements)
references
References 18 publications
13
151
0
15
Order By: Relevance
“…At present, the mainstay of the clinical management of severely ill COVID-19 patients involves intensive monitoring of the clinical status with systemic support. The mortality rate in COVID-19 is observed to be highest among the elderly patients which might be due to the age-related immune dysfunction complicated with the associated comorbidities [ [4] , [5] , [6] ]. With no effective drug available against the SARS-CoV-2 infection, the focus is on identifying existing drugs that may be effective against the virus [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the mainstay of the clinical management of severely ill COVID-19 patients involves intensive monitoring of the clinical status with systemic support. The mortality rate in COVID-19 is observed to be highest among the elderly patients which might be due to the age-related immune dysfunction complicated with the associated comorbidities [ [4] , [5] , [6] ]. With no effective drug available against the SARS-CoV-2 infection, the focus is on identifying existing drugs that may be effective against the virus [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…111 Recent studies have suggested that chronic obstructive pulmonary disease (COPD) is a major risk factor for COVID-19. 113,114 Adults with COPD exhibit upregulated ACE2 and TMPRSS2 in lung airways; asthmatic adults show slight upregulation of these genes as well. 110 An association between COVID-19 and COPD exacerbation has been noted.…”
Section: Smoking/select Chronic Respiratory Diseasesmentioning
confidence: 99%
“…and Salunke et al. had described higher morbidity and mortality rate inflicted by COVID-19 among patient with medical comorbidity including cancer [ 1 , 2 ]. Currently only symptomatic treatment and intensive care have been used for seriously ill patients.…”
Section: Introductionmentioning
confidence: 99%